EVALUASI PELAKSANAAN SUPERVISI BERBASIS PEMBELAJARAN EFEKTIF - M. Yusuf Hakim Zein; Binti Maunah; Hikmah Eva Trisnantari (STKIP Pesisir Selatan, 2026)
This research aims to identify practices in implementing effective learning-based supervision. Effective learning-based supervision is a process of coaching and professional development of teaching staff which aims to improve the quality of learning in the classroom. This research uses the library research method to analyze various relevant literature related to the implementation of effective learning-based supervision, starting from analyzing the basic concepts of effective learning-based supervision, the evaluation framework which includes aspects evaluated in the process of implementing effective learning- based supervision, then indicators of success in implementation of effective learning-based supervision as well as evaluation instruments in implementing effective learning-based supervision and this research also discusses related problems and efforts in evaluating the implementation of effective learning-based supervision. The results show that effective learning-based supervision has great potential in improving the quality of learning. However, the implementation of supervision still faces various problems in its implementation, lack of commitment from school principals or supervisors, limited time, minimal support from other teaching staff, and budget limitations. Of course, more systematic, integrated and sustainable efforts are needed to overcome these problems, including, by increasing the number of teaching staff, allocating sufficient funds, and encouraging active teacher participation.